Nilai Pendidikan Agama Hindu Dalam Tradisi Metuun Di Desa Pakraman Cekeng Kecamatan Susut Kabupaten Bangli - I Nengah Pande Pande Bawa Yasa (Jayapangus Press, 2018)
Yajna is essentially a sacred offering for the Hindus. Basically at the show of Ida Sang Hyang Widhi Wasa, the ancestors and the Rsi. Yajna based on the bond of deed or Karma which is often called this debt will always exist in every birth called Tri Rna. Tri Rna means three debts to be paid. Hindu people pay the debt is due to the sacrifice, devotion and love that delegated by Him. Metuun tradition is the ceremony of Atma Wedana whose purpose is to purify the spirit or atma that is still dirty. So Atma can be handled in Pelinggih Bhatara Hyang Guru. Based on it with all the uniqueness of society and traditions of cultural customs will also affect the ceremonies of religious ceremonies that are implemented. In addition, the ceremony is part of the three basic frameworks of Hinduism